Tribology and Dynamics of Engine and Powertrain 2010
DOI: 10.1533/9781845699932.2.470
|View full text |Cite
|
Sign up to set email alerts
|

Optimised textured surfaces with application in piston ring/cylinder liner contact

Abstract: This item was submitted to Loughborough's Institutional Repository (https://dspace.lboro.ac.uk/) by the author and is made available under the following Creative Commons Licence conditions.For the full text of this licence, please go to: http://creativecommons.org/licenses/by-nc-nd/2.5/ In: Tribology and Dynamics of Engine and Powertrain: Fundamentals, Applications and Future Trends, Edited by H. Rahnejat, Woodhead Publishing, 2010, pp. 470-517, ISBN: 978-1-84569-993-2 Chapter 14 Optimised Textured Surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…However, they indicated that the hierarchy of parameters may vary slightly under different loading conditions. In a tribological study on piston ring/cylinder liner contact, Rahmani et al investigated and optimised negative and positive type texture with different shapes in hydrodynamic lubrication. The increase of textures on the bearing surface is beneficial, and the optimised textures depend on the type, shape and geometry of the textures on the bearing surface.…”
Section: Introductionsupporting
confidence: 53%
“…However, they indicated that the hierarchy of parameters may vary slightly under different loading conditions. In a tribological study on piston ring/cylinder liner contact, Rahmani et al investigated and optimised negative and positive type texture with different shapes in hydrodynamic lubrication. The increase of textures on the bearing surface is beneficial, and the optimised textures depend on the type, shape and geometry of the textures on the bearing surface.…”
Section: Introductionsupporting
confidence: 53%
“…The method of analysis has been fully described by Balakrishnan et al 10 Analytical work by Spencer et al12 with different cross-hatch honed liners also showed that the fabricated grooves themselves act as microwedges. As already noted in the introduction, a series of analytical simulations by Rahmani et al 21 for the case of compression ring-cylinder bore contact has shown that lasertextured dimples of a conical geometry with a certain distribution, spacing and depth yield the highest load-bearing capacity, as well as reduced friction. These predictions generally agree with various experimental studies for different conjunctions.…”
Section: Results Of Textured Surfacesmentioning
confidence: 88%
“…Rahnejat et al 15 also reported a similar decrease in friction through the use of laser-ablated patterned features on the surface of the advanced coated cylinder liners in the TDC region, which are used for motor racing applications. A comprehensive analysis of various surface texture features has been given by Rahmani et al 21 Increasingly, high-performance engines and components are constructed from light alloy materials. This can drastically reduce the inertial forces developed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study did not take into account any asperity interactions in the determination of generated friction, which would be important at reversal points [18,19]. Rahmani et al [33][34] used an analytic method to optimise the feature type and pattern for a flat sliding ring. They showed that for such geometry a dimple feature of certain depth and spacing ratio yielded optimum conditions.…”
Section: Introductionmentioning
confidence: 99%